The Influence of Word of Mouth (WOM) on Customer Buying Interest with Brand Image as a Moderating Variable - Ekowati, Dhiana; Nawarcono, Winanto; Sukmarani, Wendri (CV. Media Digital Publikasi Indonesia, 2025)
Consumer purchase intention is related to word of mouth along with the increasing brand image of the company. Brand image is a brand that is based on the good and bad of the brand that consumers remember. This study aims to: (1) Analyze the influence of word of mouth on Purchase Intention and (2) Analyze how word of mouth (wom) influences Purchase Intention with brand image as a moderating variable. This study is a quantitative descriptive study. With a research sample of 100 respondents. The data collection method uses a questionnaire. The data analysis method uses MRA analysis. The results of the study show that (1) word of mouth has a positive effect on consumer Purchase Intention with a calculated t value = 10.927> t table = 1.987 with a significance value of 0.000 <0.05. This means that if the word of mouth variable increases, the purchasing decision will increase. (2) Brand image moderates the influence of word of mouth on consumer purchase interest with a regression coefficient value of the moderation variable (Word of Mouth*Brand image) of 0.588 with a positive value with a significance value of 0.032 < α (0.05).